Self-determined learning in EFL classroom: a trajectory for the future research - Deni Sapta Nugraha; Ninuk Lustyantie; Uwes Anis Chaeruman (Journal on English as a Foreign Language, 2022)
The development of technology has rapidly affected the growth complexity of the 21st century's work environment which also influences educational environment. Thus, approaches in teaching and learning such as self-determined learning has been considered relevant to enhance the quality of learning. Researchers and educators have been pursuing to accomodate the praxis of self-determined learning. The purpose of the study was to uncover research trends and try to bridge the gap of future research of self-determined learning (SDL) in the English as a foreign language (EFL) context. Using meta-synthesis, 13 selected articles were examined drawn from a single database from the last five years between 2017 and 2021. The articles were systematically selected through several criteria using the query "Self-determined Learning+AND+EFL" in the Sopus database. They contributed to the growing interest related to research and practice of heutagogy or SDL. Results showed that research areas of SDL had been widely investigated in different levels of students; primary (23%), secondary (23%), and university (54%). In addition, a few research studies were conducted to examine students' language skills and language components (listening and vocabulary) (15%). It implicated that many EFL research area could be investigated from different levels and focus in the future.